Suitability of Coral Reef Rehabilitation Sites in the Waters of Tanjung Siangau, West Bangka Regency - Wahyu Adi; Sudirman Adibrata; Umam Komarullah; Dedi Dedi; La Ode Wahidin; Zulfakar Zulfakar; Tyo Rachmana (Yayasan Serumpun Karang Konservasi, 2025)
Land clearing for mining operations can potentially cause severe damage to coastal and marine environments. Restoration of post-mining areas can be addressed through closure and recovery efforts, particularly via coral reef rehabilitation. This study aims to determine site suitability for coral reef rehabilitation or marine reclamation in the waters of Tanjung Siangau. Conducted in August 2023, the study used a multi-parameter map overlay method to produce a suitability map for reef rehabilitation. Parameters considered include bathymetry, turbidity, current velocity, wave conditions, substrate type, reef exposure, protection status, proximity to coral donor sources, community involvement, and marine spatial zoning. Findings indicate that areas damaged by coastal and marine activities require reclamation, including coral rehabilitation. Reclamation of post-mining lands must adhere to Indonesian Law No. 3 of 2020 and the Mineral and Energy Resource Ministerial Regulation No. 26 of 2018. Overlay results revealed the highest suitability score in the southern waters of Tanjung Siangau, an area categorized as moderately damaged coral cover (<50%). Local community reports indicate that this area is not mined due to the absence of tin deposits. The recommended site for coral reef rehabilitation lies outside of any licensed mining concession and is situated within an Underwater Tourism Zone in accordance with the Coastal and Small Islands Zoning Plan (RZWP3K).